A Serological And Bacteriological Study Of Leptospiral Infection In Domestic Animals In Peninsular Malaysia - Bahaman, Abdul Rani (1988)
A cross-sectional serological survey of domestic animals in Wes t Malaysia revealed that 2 5 . 5 percent of the animals examined had agglutinating antibodies to one or more antigens belonging to Leptospira interrogans . Significant prevalence of infection was observed in cattle ( 40 . 5 % ) , buffaloes ( 31 % ) and pigs ( 16% ) .The Sejroe and Pomona serogroups were the principal one s involved whilst infections to the other eight serogroups appeared insignificant and were indicative of sporadic infection . Majority of the large cattle and buffalo farms demonstrated high prevalences of leptospiral infection . Amongst cattle , the droughtmasters had the highest prevalence whilst the Kedah-Kelantan ( an indigenous breed ) had the lowest prevalence of leptospiral infection . Leptospiral infection in goats and sheep was shown to be sporadic . A bacteriological survey of cattle revealed 18.9 percent ( 42 /222 ) had leptospiral infection . Isolates were obtained from all herds except one . Six leptospiral serovars , namely , canicola, australis, javanica, ballum, pomona and hardjo were isolated for the first time in cattle in Malaysia . An isolate obtained from a bovine kidney proved to be a new serovar and was given the name. unipertama . The small number of buffalo urine samples examined were all negative on culture.